2021
DOI: 10.1111/tri.13832
|View full text |Cite
|
Sign up to set email alerts
|

Solid organ donor–recipient race‐matching: analysis of the United Network for Organ Sharing database

Abstract: Summary Donor ethnicity is a prognosticator in organ transplant. However, the impact of donor/recipient race‐matching is unclear. We hypothesized that there would be increased survival in donor–recipient race‐matched organ recipients because of genetic and physiologic similarities. The UNOS database from 1999 to 2018 was queried for all solid organ transplantations including heart, lung, liver, kidney, and pancreas transplants. Data were sorted by donor and recipient race into matched and unmatched categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…LeClaire et al (11) conducted an analysis of solid organ (including heart, lung, liver, kidney, and pancreas) transplantations from the UNOS database and reported that patient survival in KT was not influenced by race-matching, but race-unmatched African Americans experienced shorter graft survival at all time points after controlling for potential confounders, which was inconsistent with our results. In our results, the crude patient and graft survival rates in racematching were significantly higher than those in raceunmatching.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…LeClaire et al (11) conducted an analysis of solid organ (including heart, lung, liver, kidney, and pancreas) transplantations from the UNOS database and reported that patient survival in KT was not influenced by race-matching, but race-unmatched African Americans experienced shorter graft survival at all time points after controlling for potential confounders, which was inconsistent with our results. In our results, the crude patient and graft survival rates in racematching were significantly higher than those in raceunmatching.…”
Section: Discussioncontrasting
confidence: 99%
“…Donor-recipient race-matching is considered a potential prognostic factor for organ transplant outcomes, since receiving organs from the same race increases the possibility of genetic and physiological similarities between donors and recipients and thereby reduces the possibility of rejection events (7). However, few studies (8)(9)(10)(11)(12) have investigated the impact of donor-recipient race-matching on post-transplant survival, especially in KT. Although some studies have noted reduced survival of patients or grafts in race-unmatched organ transplantation, conflicting results have been reported in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that race-matched status was not significant to DGF, graft failure, acute rejection, or mortality. LeClaire et al 18 conducted a study that also explored the effects of race-matching using the OPTN database, and their study included adults who underwent heart, lung, liver, kidney, and pancreas transplants. 18 There were slight variations in some organ transplant outcomes due to race-matching, but the results were not strong enough to suggest race-matching should be considered when matching donors and recipients.…”
Section: Discussionmentioning
confidence: 99%
“…LeClaire et al 18 conducted a study that also explored the effects of race-matching using the OPTN database, and their study included adults who underwent heart, lung, liver, kidney, and pancreas transplants. 18 There were slight variations in some organ transplant outcomes due to race-matching, but the results were not strong enough to suggest race-matching should be considered when matching donors and recipients. Contrary findings resulted from Allen et al’s study, 26 which also used the OPTN database and found that race-matching of adult liver transplant pairs resulted in improved long-term survival but did not confer any advantages for decreased rejection after 1 y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation